Adolescent survey non-response and later risk of death. A prospective cohort study of 78 609 persons with 11-year follow-up - Parkkari Jari; Mattila Ville M; Rimpelä Arja (BMC, 2007)
Abstract Background Non-response in survey studies is a growing problem and, being usually selective, it leads to under- or overestimation of health outcomes in the follow-up. We followed both respondents and non-respondents by registry linkage to determine whether there is a risk of death, related to non-response at baseline. Methods Sample data of biennial surveys to 12-18-year-old Finns in 1979-1997 were linked with national death registry up to 2001. The number of respondents was 62 528 (79.6%) and non-respondents 16 081 (20.4%). The average follow-up was 11.1 years, totalling 876 400 person-years. The risk of death between non-respondents and respondents was estimated by hazard ratios (HR). Results The number of deaths per 100 000 person-years were 229 in non-respondents and 447 in respondents (HR 2.0, 95% CI: 1.5-2.6). The hazard ratios of death were for intoxication 3.2 (95% CI: 1.9-5.4), for disease 3.1 (95% CI: 2.2-4.1), for violence-related injury 2.0 (95% CI: 1.5-2.6) and for unintentional injury 1.8 (95% CI: 1.3-2.4) in non-respondents vs. respondents. The association between non-response and death increased with age at baseline, and the increase persisted after the age of 25. Conclusion Our study demonstrated significantly increased rates of death among adolescent non-respondents in a follow-up. The highest hazard ratios were seen in disease- and violence-related deaths. The death rate varied between respondents and non-respondents by death type. Increased rates of death persisted beyond the age of 25.